Superficial Femoral Artery Aneurysmal Degeneration - Sixteen years after superficial femoral artery endarterectomy and vein patch angioplasty - Teixeira,Gabriela (2019)
Superficial femoral artery (SFA) aneurysms are rare clinical disorders, with few case reports and small series published concerning atherosclerotic aneurysms. We report a clinical case a giant aneurysm of the SFA, in a patient previously submitted to extensive SFA endarterectomy and vein angioplasty. A 73-year-old man presented at a routine vascular surgery consultation. The patient had been submitted to a right SFA endartectomy and vein patch angioplasty, sixteen years ago, for intermittent claudication. Physical examination demonstrated a large pulsatile mass of the right thigh. His right pedal pulse was palpable. Ultrasound and computed tomography scan confirmed a 78x71x240mm aneurysm of the right superficial femoral artery. He was proposed to aneurysmectomy and femoro-popliteal bypass. During operative intervention, proximal and distal control was obtained and the aneurysm opened. A large amount of thrombus was removed and a femoro-popliteal bypass was performed using the ipsilateral great saphenous vein. The postoperative period was uneventful, as was the patient recovery. In our report, the aneurysmal area matched precisely to the endarterectomised area and no other aneurysms were found. So we are facing an uncommon case of a SFA degeneration into a giant aneurysm after extensive endarterectomy and vein angioplasty.